Trajectories of intellectuals and cultural networks in the Peruvian Amazon between 1940 and 1980 - Herrera, Morgana (2019)
national culture, particularly from an intellectual and literary history perspective. Within the pantheon of authors and thinkers who are part of what has been defined as a Peruvian intellectual canon, those who define themselves as Amazonians are usually absent from it. However, several intellectuals have worked for the dissemination of their culture from the Amazon. This work brings together three studies of intellectual trajectories and strategies of three Amazonian authors: Francisco Izquierdo Ríos, Javier Dávila Durand and Arnaldo Panaifo Teixeira.